2017
DOI: 10.20319/pijss.2017.31.332345
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies Teachers’ and Teacher Candidates’ Perceptions on Prompt Feedback and Communicate High Expectations

Abstract: This study aims to investigate perception of social studies teachers and teacher candidates on the implication of two of the seven principles of good practice in education developed by Chickering and Gamson (1987)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…The emphasis in this study is to understand the influence of prompt feedback on satisfaction. Feedback gives the information about the students' effective performance (Chang, 2011;Grebennikov & Shah, 2013;Simsek et al, 2017). Prompt feedback enhances student learning experience (Brownlee et al, 2009) and boosts satisfaction (O'donovan, 2017).…”
Section: Prompt Feedback and Satisfaction Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emphasis in this study is to understand the influence of prompt feedback on satisfaction. Feedback gives the information about the students' effective performance (Chang, 2011;Grebennikov & Shah, 2013;Simsek et al, 2017). Prompt feedback enhances student learning experience (Brownlee et al, 2009) and boosts satisfaction (O'donovan, 2017).…”
Section: Prompt Feedback and Satisfaction Of Studentsmentioning
confidence: 99%
“…Christensen (2014) studied linking feedback to performance and introduced the positivity ratio concept, which is a mechanism that plays an important role in finding out the performance through feedback. It has been found that prompt feedback helps in developing a strong linkage between faculty and students which ultimately leads to better learning outcomes (Simsek et al, 2017;Chang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly important factor influencing the level of student satisfaction is quick feedback (Kinicki et al, 2004), information provided by lecturers and tutors about student performance. Rapid feedback has been found to help create a strong link between academic staff and students, ultimately leading to better learning outcomes (Simsek et al, 2017;Chang, 2011). As research results show, academic staff members who respond quickly to questions and provide timely feedback on assignments tend to help students in online courses improve interaction, actively participate, focus on results, and understand study material (Martin, 2020).…”
Section: Student Satisfactionmentioning
confidence: 99%
“…The learner"s role is to construct new ideas from current and past knowledge. Simsek et al (2017) enumerated the basic characteristics of constructivist learning environments to include active learning; authentic instructional tasks; cooperation between students; and diverse and multiple learning formats. The instructional process in social studies is similar to what is obtainable in other subjects in social sciences.…”
Section: Pupil: International Journal Of Teaching Education and Learning Issn 2457-0648mentioning
confidence: 99%